2012
DOI: 10.1088/0256-307x/29/7/071401
|View full text |Cite
|
Sign up to set email alerts
|

Weak Decays of First Radial Excited D q (2 S ) and B q (2 S ) States

Abstract: We study the exclusive semileptonic and nonleptonic decays of the first radial excited heavy-light pseudoscalars đ·đ‘ž(2𝑆) and đ”đ‘ž(2𝑆) (𝑞 = 𝑱, 𝑑, 𝑠) with the improved Bethe-Salpeter (B-S) method which takes into account the relativistic effects in wave functions and transition matrix elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
326
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(353 citation statements)
references
References 25 publications
(12 reference statements)
22
326
0
5
Order By: Relevance
“…In the literature, it has been reported that the addition of Ce increases Ni dispersion. [27,28] However, the surface atomic concentration for the catalyst presented in this work shows a decrease of about 60% for Cecontaining catalysts and 10% for Pr ones. Besides, the metallic dispersion for the Ce-containing catalysts increases or remains constant after reduction, whereas those with Pr decrease.…”
Section: Resultsmentioning
confidence: 74%
“…In the literature, it has been reported that the addition of Ce increases Ni dispersion. [27,28] However, the surface atomic concentration for the catalyst presented in this work shows a decrease of about 60% for Cecontaining catalysts and 10% for Pr ones. Besides, the metallic dispersion for the Ce-containing catalysts increases or remains constant after reduction, whereas those with Pr decrease.…”
Section: Resultsmentioning
confidence: 74%
“…Many studies have reported that the addition of a second metal (even if it is inactive by itself) can significantly improve the activity and selectivity of a reaction by enhancing the stability of the catalyst through the synergistic effect of two metals. [25][26][27][28] Bimetallic catalysis has great potential for developing versatile reaction conditions [29][30] and studies on bimetallic catalytic reactions have attracted more attention over the past few decades. [31][32] Recently, many research groups reported that bimetallic catalyst benefits the carbonylation of organics, [30,[33][34] leading us to consider that a bimetallic catalyst can also promote acetylene hydration.…”
Section: Introductionmentioning
confidence: 99%
“…As possible next-generation sensitizers, semiconductors have many advantages such as facile tunability of effective band gaps, high stability and inertness toward atmospheric oxygen and water, and possibilities of using the materials to construct novel structures such as multilayered-sensitizers or hybrid-sensitizers. [20] Until now, some deposition techniques have been developed to prepare the compound film, such as chemical vapor deposition, [21] electrodeposition, [22] chemical bath deposition, [23] and atomic layer deposition. [24,25] Among them, chemical bath deposition is a simpler method and less expensive than other compound film deposition techniques.…”
Section: Introductionmentioning
confidence: 99%